Effective reduction of Salmonella Enteritidis in broiler chickens using the UPWr_S134 phage cocktail - Kuźmińska-Bajor, Marta; Śliwka, Paulina; Korzeniowski, Paweł; Kuczkowski, Maciej; Moreno, David Sáez; Woźniak-Biel, Anna; Śliwińska, Emilia; Grzymajło, Krzysztof (Frontiers in Microbiology, 2023)
Salmonella is a poultry-associated pathogen that is considered one of the most important zoonotic bacterial agents of contaminated food of animal origin including poultry products. Many efforts are taken to eliminate it from the food chain, and phages are one of the most promising tools to control Salmonella in poultry production. We investigated the usefulness of the UPWr_S134 phage cocktail in reducing Salmonella in broiler chickens. For this purpose, we analyzed the survivability of phages in the harsh environment encountered in the chicken gastrointestinal tract, which has low pH, high temperatures, and digestive activity. Phages in the cocktail UPWr_S134 showed the ability to remain active after storage at temperatures ranging from 4 to 42°C, reflecting temperatures of storage conditions, broiler handling, and the chicken body, and exhibited robust pH stability. We found that although simulated gastric fluids (SGF) caused phage inactivation, the addition of feed to gastric juice allows maintenance of UPWr_S134 phage cocktail activity. Further, we analyzed UPWr_S134 phage cocktail anti-Salmonella activity in live animals such as mice and broilers. In an acute infection model in mice, the application of doses of 107 and 1014 PFU/ml UPWr_S134 phage cocktail resulted in delaying symptoms of intrinsic infection in all analyzed treatment schedules. In Salmonella-infected chickens orally treated with the UPWr_S134 phage cocktail the number of pathogens in internal organs in comparison to untreated birds was significantly lower. Therefore we concluded that the UPWr_S134 phage cocktail could be an effective tool against this pathogen in the poultry industry.